Pengaruh Harga Diskon, Penilaian Produk dan Layanan COD terhadap Keputusan Pembelian (Studi pada E-commerce Shopee di Sidoarjo) - Wiradinata, Rigianda Syahrul Akbar; Yulianto, Rizal (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to investigate the impact of discount prices, product ratings, and COD (Cash on Delivery) services on purchasing decisions on the Shopee E-commerce platform in Sidoarjo. Data was collected through a survey using a questionnaire filled in by 100 respondents. To test the relationship between the independent variables (discount price, product assessment, and COD service) and the dependent variable (purchase decision), multiple linear regression analysis was used. The results of the analysis show that discount prices have a significant influence on purchasing decisions at Shopee Sidoarjo, with a significance value of 0.000 (<0.05) in the T test. This means that the bigger the discount offered, the higher the consumer's possibility of making a purchase. Product ratings also have a significant influence on purchasing decisions, with a significance value of 0.047 (<0.05) in the T test. This shows that consumers tend to buy products with good ratings. COD services show a significant influence on purchasing decisions with a significance value of 0.000 (<0.05) in the T test, indicating that the availability of COD services can increase consumer purchasing decisions. This research provides important insights for E-commerce companies about the factors that influence consumer purchasing decisions in online marketplaces. These findings emphasize the importance of effective discount pricing strategies, improving product quality, and providing convenient payment options such as COD services to improve purchasing decisions and expand market share in an increasingly competitive E-commerce market.